2005
DOI: 10.1016/j.bandc.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The BOLD response during Stroop task-like inhibition paradigms: Effects of task difficulty and task-relevant modality

Abstract: . (2005) 'The BOLD response during Stroop task-like inhibition paradigms : eects of task diculty and task-relevant modality.', Brain and cognition., 59 (1). pp. 23-37. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 60 publications
2
23
2
Order By: Relevance
“…In agreement with previous studies [Brass et al, 2004;Davie et al, 1999;De Stefano et al, 2006;Droogan et al, 1999;Falini et al, 1998;Filippi et al, 1996;Horsfield et al, 1996;Traboulsee et al, 2003], we found a relatively high proportion of T 2 -visible lesions in these patients and widespread abnormalities in the NABTs. Consistent with previous studies reporting the Stroop effect on fMRI activations in healthy people [Bench et al, 1993;Carter et al, 1995;Mitchell, 2005;Pardo et al, 1990], both groups of subjects showed the activation of several areas located in the frontal (PFC, ACC, and IFG) and parietal lobes (IPL and postcentral gyrus), and the cerebellum during the interference and facilitation conditions. The PFC and ACC have been implicated in interference processing/response inhibition, which is an important component of the Stroop task [Carter et al, 1995;Pardo et al, 1990].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with previous studies [Brass et al, 2004;Davie et al, 1999;De Stefano et al, 2006;Droogan et al, 1999;Falini et al, 1998;Filippi et al, 1996;Horsfield et al, 1996;Traboulsee et al, 2003], we found a relatively high proportion of T 2 -visible lesions in these patients and widespread abnormalities in the NABTs. Consistent with previous studies reporting the Stroop effect on fMRI activations in healthy people [Bench et al, 1993;Carter et al, 1995;Mitchell, 2005;Pardo et al, 1990], both groups of subjects showed the activation of several areas located in the frontal (PFC, ACC, and IFG) and parietal lobes (IPL and postcentral gyrus), and the cerebellum during the interference and facilitation conditions. The PFC and ACC have been implicated in interference processing/response inhibition, which is an important component of the Stroop task [Carter et al, 1995;Pardo et al, 1990].…”
Section: Discussionsupporting
confidence: 91%
“…Participants viewed the screen through an angled mirror on the head coil. Since it has been suggested that in the Stroop task paradigms a manual response is a more accurate indicator of the effect of task condition than a verbal response [Barch et al, 2001;Mitchell, 2005] and to avoid movements during vocalization of the response, subjects were given standardized instruction to indicate the color of the ink in which the presented words were printed via an MRI compatible four-buttons response-box, which recorded both accuracy of response and reaction times (RT), held in their R hand. All participants were instructed carefully to respond to the colour of the word and ignore its content.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…There were two common effects in the Stroop task: first, the interference effect refers to the observation that subjects have more difficulty in answering incongruent trials with respect to neutral trials. Second, the facilitation effect comes from the observation that subjects respond quicker to congruent trials compared to neutral trials [29]. Although the interference effect was evident in RTs, we could not observe a facilitation effect.…”
Section: A Behavioral Resultscontrasting
confidence: 58%
“…Diffusion tensor imaging (DTI) identified connectivity of the pre-SMA to the PMd and PMv (Hartwigsen et al, 2013), Figure 4 A summary of activity foci from 24 fMRI studies of behavioral tasks and with contrasts of switch > no switch (green) in set/response switching task (De Baene & Brass, 2013;Dove et al, 2000;Moll et al, 2002;Witt & Stevens, 2012;Woodward et al, 2006); incongruent > congruent (blue) in Stroop, Simons, or Flanker task (Fan et al, 2008;Kemmotsu et al, 2005;Liu et al, 2004;Liu et al, 2014;Luks et al, 2007;McNab et al, 2008;Mitchell, 2005;Sebastian et al, 2013;Zysset et al, 2007); no-go > go (red) in go/no-go task (Brown et al, 2008;Horn et al, 2003;Kelly et al, 2004;McNab et al, 2008;Nakata et al, 2008;Passamonti et al, 2006;Sebastian et al, 2013;Steele et al, 2013) Broca's area of the IFC (Jenabi et al, 2013), and the lateral prefrontal cortex (lPFC) (Johansen-Berg et al, 2004). DTI also confirmed pre-SMA projections to the striatum at locations rostral to SMA projections (Lehéricy et al, 2004).…”
Section: Presupplementary Motor Areamentioning
confidence: 99%